2021
DOI: 10.21203/rs.3.rs-145211/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleeping During the First Wave: Demographic, Psychological, Chronobiological, and Work-Related Predictors of Sleep Disturbances Throughout the COVID-19 Lockdown

Abstract: The first COVID-19 contagion wave caused unprecedented restraining measures worldwide. In Italy, a period of generalized lockdown involving home confinement of the entire population was imposed for almost two months (9 March–3 May 2020). The present is the most extensive investigation aimed to unravel the demographic, psychological, chronobiological, and work-related predictors of sleep disturbances throughout the pandemic emergency. A total of 13989 Italians completed a web-based survey during the confinement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…The present investigation confirmed the vulnerability of women to experience sleep ad psychological problems during the pandemic (Daly et al, 2020;Rossi et al, 2020;Salfi et al, 2020;Salfi, Lauriola, et al, 2021). However, we did not detect differences between genders in the trajectories of sleep quality, insomnia, depression, and anxiety symptoms across the three survey waves.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The present investigation confirmed the vulnerability of women to experience sleep ad psychological problems during the pandemic (Daly et al, 2020;Rossi et al, 2020;Salfi et al, 2020;Salfi, Lauriola, et al, 2021). However, we did not detect differences between genders in the trajectories of sleep quality, insomnia, depression, and anxiety symptoms across the three survey waves.…”
Section: Discussionsupporting
confidence: 81%
“…The current literature consistently showed that age groups (Amicucci et al, 2021;Bottary et al, 2022;Daly et al, 2020;Jahrami et al, 2022;Rossi et al, 2020), genders (Daly et al, 2020;Rossi et al, 2020;Salfi et al, 2020;Salfi, Lauriola, et al, 2021), and chronotypes (Bottary et al, 2022;Merikanto et al, 2022;Salfi, Lauriola, et al, 2021) reacted differently to the first months of restraining measures. Specifically, younger people (Amicucci et al, 2021;Daly et al, 2020;Jahrami et al, 2022;Rossi et al, 2020) and women (Daly et al, 2020;Rossi et al, 2020;Salfi et al, 2020;Salfi, Lauriola, et al, 2021) reported higher rates of sleep disturbances and psychological symptoms. These results were confirmed by Italian and European studies (Benke et al, 2022;Chodkiewicz et al, 2021;Rus Prelog et al, 2022;Wetherall et al, 2022) addressing the effect of the second wave of COVID-19.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, further research directions performing longitudinal and case-control studies with larger sample sizes, including as potential variables the concomitant COVID-19 infection during pregnancy and/or postpartum period, should be conducted to better evaluate whether the gendereffect might explain the increased levels of depression in pregnant and/or postpartum women during the COVID-19 pandemic, as already reported in previous Italian studies which observed more severe psychological symptoms during the COVID-19 pandemic reported by females compared to males in Italian population (84)(85)(86). In fact, "caution is needed when reporting opinions or data coming from cross-sectional studies, especially in the absence of proper controls for lockdown" (87).…”
Section: Discussionmentioning
confidence: 89%